2010
DOI: 10.1016/j.euroecorev.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of overdissipation in the all pay auction

Abstract: Pervasive overbidding represents a well-documented feature of all-pay auctions. Aggregate bids exceed Nash predictions in laboratory experiments, and individuals often submit bids that guarantee negative profits. This paper examines three factors that may reduce pervasive overbidding: (a) repetition (experience), (b) reputation (strangers vs. partners) and (c) active participation. We find that aggregate over-dissipation diminishes but is not eliminated with repetition, and that repetition, in conjunction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 37 publications
1
46
2
Order By: Relevance
“…Their important finding carries over to symmetric all-pay auctions. Indeed, except for Potters et al (1998), the majority of studies using symmetric all-pay auctions with complete information also find that session averages reflect overbidding (Gneezy and Smorodinsky, 2006;Lugovskyy et al, 2010;Fehr and Schmidt, 2011;Klose and Sheremeta, 2012;Ernst and Thöni, 2013;Ong and Chen, 2013). While Potters et al find evidence of equilibrium play in their two-player all-pay auction experiment, their design imposed an exogenous cap on bids (15% above the prize value), which may have biased behavior toward lower, equilibrium bids.…”
Section: All-pay Auctionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Their important finding carries over to symmetric all-pay auctions. Indeed, except for Potters et al (1998), the majority of studies using symmetric all-pay auctions with complete information also find that session averages reflect overbidding (Gneezy and Smorodinsky, 2006;Lugovskyy et al, 2010;Fehr and Schmidt, 2011;Klose and Sheremeta, 2012;Ernst and Thöni, 2013;Ong and Chen, 2013). While Potters et al find evidence of equilibrium play in their two-player all-pay auction experiment, their design imposed an exogenous cap on bids (15% above the prize value), which may have biased behavior toward lower, equilibrium bids.…”
Section: All-pay Auctionsmentioning
confidence: 85%
“…A utility function based on these assumptions gives rise to a bimodal bidding behavior in the equilibrium of an all-pay auction. Lugovskyy et al (2010) further explore observed deviations from Nash equilibrium in all-pay auctions. In long sessions, lasting 60 periods, with fixed matching of four-player groups, they show that learning seems to bring bids closer to the Nash equilibrium prediction in the aggregate.…”
Section: All-pay Auctionsmentioning
confidence: 99%
“…provides further support for the view that in the type of cutthroat competition represented by the all-pay auction, the high degree of overdissipation that occurs in experiments with four or more players (see Davis and Reilly, 1998, Gneezy and Smorodinsky, 2006, and Lugovskyy et al, 2010 does not arise with two players.…”
mentioning
confidence: 64%
“…In the other two treatments, average revenue falls from roughly 1.75 and 2.15 times the value of the prize in the first ten periods to 1.15 and 1.25 in the last ten periods. See Lugovskyy et al (2010), Figure 2,p. 980.…”
mentioning
confidence: 99%
“…While this literature puts much emphasis on tournaments, Tullock contests and incomplete information allpay auctions, only a few papers focus on complete information all-pay auctions (e.g., Davis and Reilly 1998, Gneezy and Smorodinsky 2006, Lugovskyy, Puzello, and Tucker 2010or Ernst and Thöni 2013. 3 In all-pay auctions with complete information all equilibria are in mixed strategies, and with the exception of Davis and Reilly (1998) all these papers investigate symmetric all-pay auctions.…”
Section: Introductionmentioning
confidence: 99%